Levers to reconcile cured meat products with health concerns and culinary heritage - Véronique Santé-Lhoutellier (Italian Journal of Animal Science)
The preservation of meat by methods such as salting, drying and/or smoking is ancestral and is linked to culinary heritage, through the geographical anchorage. These features and the associated know-how are the basis for the construction and recognition of quality signs that guarantee and certify certain commitments. Nevertheless, current scientific evidence shows that the consumption or particularly the over-consumption of certain meat products is conducive to the development of health problems. This raises the question of how to make these foods healthier without betraying their identity. This review addresses the possible levers.